1997
DOI: 10.1021/jp9712866
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Translational and Reorientational Motions of Planar Nickel Complex Ions

Abstract: The translational diffusion constants, DT , of the bis(maleonitriledithiolato)nickel anion and dianion, Ni(mnt)2 - and Ni(mnt)2 2-, respectively, have been measured in acetone and ethyl alcohol solutions drawn through a microcapillary by reduced pressure at 25 °C. The translational radius, r t, obtained from DT is larger for Ni(mnt)2 2- than for Ni(mnt)2 - in both solvents. The larger r t for Ni(mnt)2 2- is attributed to ion pairing with (n-Bu)4N+, while Ni(mnt)2 - does not appear to be ion paired. r t for Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
44
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(56 citation statements)
references
References 29 publications
12
44
0
Order By: Relevance
“…The r t values for [Ni(mnt) 2 ] − are essentially the same in acetonitrile (ACN), EtOH, acetone, and BuOH (≈3.60 Å) and are smaller than those for [Ni(mnt) 2 ] 2− in EtOH, acetone, and ACN (≈4.50 Å). 16,31 These results are in agreement with electrochemical, 32 conductivity, 33,34 and vapor phase osmometry 32 data in ACN that showed [Ni(mnt) 2 ] 2− but not [Ni(mnt) 2 ] − was ion-paired with Et 4 N + (we used Bu 4 N + ). The absence of ion pairing between [Ni(mnt) 2 ] − and Bu 4 N + in diglyme is consistent with infrared studies that indicated a lack of association between Bu 4 N + and CF 3 SO 3 − in both diglyme 35 and triglyme 36 (triethylene glycol dimethyl ether).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The r t values for [Ni(mnt) 2 ] − are essentially the same in acetonitrile (ACN), EtOH, acetone, and BuOH (≈3.60 Å) and are smaller than those for [Ni(mnt) 2 ] 2− in EtOH, acetone, and ACN (≈4.50 Å). 16,31 These results are in agreement with electrochemical, 32 conductivity, 33,34 and vapor phase osmometry 32 data in ACN that showed [Ni(mnt) 2 ] 2− but not [Ni(mnt) 2 ] − was ion-paired with Et 4 N + (we used Bu 4 N + ). The absence of ion pairing between [Ni(mnt) 2 ] − and Bu 4 N + in diglyme is consistent with infrared studies that indicated a lack of association between Bu 4 N + and CF 3 SO 3 − in both diglyme 35 and triglyme 36 (triethylene glycol dimethyl ether).…”
Section: Discussionsupporting
confidence: 88%
“…Simulation of the trianion’s glassy spectrum in diglyme gave g x = 2.0824, g y = 2.0660, and g z = 2.2053 (with relative uncertainties of ±0.0010); details of their determination, the spectrometer, and other aspects of the ESR methods are given in refs 15 and 16. The assignment of the g factors to molecular axes (Figure 1) is by analogy with single crystal results 8 for [Cu(mnt) 2 ] 2− , which like [Ni(mnt) 2 ] 3− , has a formally d 9 metal ion.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of the spectra show that, as in our previous solvents, 8,9 Ni(mnt) 2 − is reorienting with D || = D y and D || / D ⊥ ≈ 3.0. The values of τ 2 (0) can be fitted using eq 1, 11 and as discussed below, the values of C ⊥ and κ ⊥ indicate relatively strong solute–solvent interactions.…”
Section: Introductionsupporting
confidence: 74%
“…9 The values of C ⊥ and κ ⊥ in the above solvents 8,9 are given in Table 1 and differ by more than a factor of 3, showing that the viscosity is not the only solvent property determining the reorientation of Ni(mnt) 2 − .…”
Section: Introductionmentioning
confidence: 98%
“…A detection wavelength of 260 nm was used for toluene in hexane. Other aspects of the instrumentation and data gathering are described in ref 17.…”
Section: Methodsmentioning
confidence: 99%